2020
DOI: 10.3389/fvets.2020.00035
|View full text |Cite
|
Sign up to set email alerts
|

Current Standards and Practices Within the Therapy Dog Industry: Results of a Representative Survey of United States Therapy Dog Organizations

Abstract: Organizations that deliver animal-assisted interventions (AAIs), as well as those that train, evaluate, and register therapy dogs, have proliferated in recent decades in the United States (U.S.). Each of these organizations has its own policies and procedures for screening, evaluating, and instructing dogs and their owners/handlers, but little is currently known about the range of different practices that exist nationwide. The aim of this project was to survey a representative, national sample of U.S. therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 29 publications
1
41
1
1
Order By: Relevance
“…Both SCAS and AAII have renewed their guidelines in 2019 [ 6 , 7 ]; see also the International Association of Human-Animal Interaction Organizations (IAHAIO) White Paper 2018 [ 8 ]. Serpell et al [ 9 ] provide a recent representative survey of current standards and differing practices in the USA. It is noteworthy that in the US, and around the world, many organisations have set some guidelines and policies as to how they prefer to work, but guidance and actual practices differ.…”
Section: Introductionmentioning
confidence: 99%
“…Both SCAS and AAII have renewed their guidelines in 2019 [ 6 , 7 ]; see also the International Association of Human-Animal Interaction Organizations (IAHAIO) White Paper 2018 [ 8 ]. Serpell et al [ 9 ] provide a recent representative survey of current standards and differing practices in the USA. It is noteworthy that in the US, and around the world, many organisations have set some guidelines and policies as to how they prefer to work, but guidance and actual practices differ.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly alarming, the survey found 70% of therapy dog organizations surveyed permitted dogs to be fed a raw meat diet. A nationally representative survey of U.S. therapy dog organization practices reported similar results of inconsistent practices that may risk human health and canine welfare ( 55 ). Results also revealed a concerning number of organizations failing to limit raw meat diets and treats and failing to place time limits on therapy dog visits.…”
Section: Issues and Challengesmentioning
confidence: 92%
“…However, literature searches most often result in articles and research related to AAA, police/military working dog, or assistance dog traits or preparation processes and are frequently used to fill the void in AAT-specific content [ 41 , 42 ]. This, in and of itself, can be problematic because without an overarching, regulatory body to oversee policies and procedures for evaluation, most organizations develop their own [ 43 ]. It is therefore not surprising that a national 2020 study of nearly three dozen AAA evaluation and registration organizations found no consensus on several factors relating to the criterion for passing evaluation [ 43 ].…”
Section: Part 1: the Unique Character Of Animal-assisted Therapy Wmentioning
confidence: 99%
“…This, in and of itself, can be problematic because without an overarching, regulatory body to oversee policies and procedures for evaluation, most organizations develop their own [ 43 ]. It is therefore not surprising that a national 2020 study of nearly three dozen AAA evaluation and registration organizations found no consensus on several factors relating to the criterion for passing evaluation [ 43 ]. This included the length of time a dog lived with the handler prior to evaluation, the frequency of re-evaluation of the dog, vaccination requirements, amount of time and frequency of visits, restriction of activity if the dog showed signs of illness, or appropriate humane training methods [ 43 ].…”
Section: Part 1: the Unique Character Of Animal-assisted Therapy Wmentioning
confidence: 99%